Preparation of Peapod‐Like Nano‐Copolymers with Periodic Sequence via Polymerization‐Induced Morphology Differentiation and Fusion - Yin, De‐Peng; Zhao, Xin‐Yue; Cheng, Jia‐Min; Zhu, Ren‐Man; Liu, Chao; Hong, Chun‐Yan (Angewandte Chemie International Edition, 2025)
Inorganic nanoparticles have so far dominated the field of nanoparticle assembly, and assembly of pure organic nanoparticles (such as block copolymer nanoparticles) has rarely been examined in colloidal systems. Expanding the scope of nanoparticles is of great significance for the study of nanoparticle assembly. Herein, a paradigm for the copolymerization of organic nanoparticles into peapod‐like linear nanostructures with periodic sequence is introduced. Vesicles and porous spheres are generated in situ during polymerization‐induced self‐assembly (PISA) and can be viewed as nanoscale monomers (“nanomers”). The subsequent copolymerization of these nanomers is completed in one‐pot, which greatly simplifies the preparation of nanomers and peapod‐like nano‐copolymers. It is demonstrated that appropriate π–π stacking interactions are crucial to the formation of nanomers and their copolymerization progress. Notably, the research subjects in nano‐copolymers with periodic sequence have expanded to organic nanoparticles, which is beneficial to further expand the horizons of nanoparticle assembly. Moreover, the multiple separated compartments in the peapod‐like nano‐copolymers will open new directions toward development of artificial organelle and on‐demand catalysis in different compartments within the same nano‐object. We report a novel strategy for constructing peapod‐like nano‐copolymers with periodic sequence through fusion of vesicles and porous spheres. The generation and assembly of vesicles and porous spheres are achieved via polymerization‐induced self‐assembly (PISA) in one‐pot. The aggregation unit numbers of peapod‐like nano‐copolymers are affected by the length of solvophobic block and collision probability of vesicles and porous spheres.